Influence of nutrition in the treatment and prevention of mental disorders: anxiety and depression (Research, Society and Development, 2022)
Introduction: Anxiety and depression disorders affect a large part of the population and their causes are varied. One of them is inadequate nutrition. In general, intake of fruits, vegetables and fiber is associated with the richness and diversity of the microbiota, while increased intake of processed foods (high in fat and sugar) increases the risk of chronic inflammatory diseases such as depression. Objective: to describe the influence of nutrition in the treatment and prevention of mental disorders: anxiety and depression. Methodology: descriptive and qualitative literature review. Results: individuals with these disorders have nutritional deficiencies of certain substances and, with adequate nutrition, can recover from depression and anxiety. Conclusion: there is a direct relationship between what we eat and mental health and food helps in the treatment of these disorders.